2020
DOI: 10.1177/0961203320972799
|View full text |Cite
|
Sign up to set email alerts
|

CD14 (C-159T) polymorphism is associated with increased susceptibility to SLE, and plasma levels of soluble CD14 is a novel biomarker of disease activity: A hospital-based case-control study

Abstract: Background Cluster of differentiation 14 (CD14) plays a crucial role in the innate immune response of the host in protection against various pathogens. The importance of soluble CD14 in autoimmune disorders has been described in different populations. However, the role of sCD14 in systemic lupus erythematosus (SLE) is poorly understood. Further, the association of functional variants at the promoter region of the CD14 gene (−159 C > T) with susceptibility to SLE or disease severity needs to be defined. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The minor T allele frequencies in this study population and their significant association with different diseases are mentioned. The recent study from the eastern part (Odisha state) of India in all female subjects has shown an association of rs2569190 (C/T) SNP to increased predisposition to lupus (SLE) and the T-allele frequency was 0.46 for healthy control and 0.58 for SLE cases ( 37 ). The MAF (T allele) in other Indian studies are: West Bengal ( 38 ), 0.53, control vs. 0.49, Asthma case; Chennai ( 39 ), 0.43 in Control vs. 0.54 in Chronic periodontitis case; Hyderabad, Andhra Pradesh ( 40 ), 0.41 in Control vs. 0.53 in Ulcerative Colitis case; Chandigarh ( 41 ), 0.5 in Control vs. 0.64 in NAFLD case; and Lucknow, UP ( 42 ), 0.65 in healthy Control vs. 0.54 in CAD cases.…”
Section: Discussionmentioning
confidence: 99%
“…The minor T allele frequencies in this study population and their significant association with different diseases are mentioned. The recent study from the eastern part (Odisha state) of India in all female subjects has shown an association of rs2569190 (C/T) SNP to increased predisposition to lupus (SLE) and the T-allele frequency was 0.46 for healthy control and 0.58 for SLE cases ( 37 ). The MAF (T allele) in other Indian studies are: West Bengal ( 38 ), 0.53, control vs. 0.49, Asthma case; Chennai ( 39 ), 0.43 in Control vs. 0.54 in Chronic periodontitis case; Hyderabad, Andhra Pradesh ( 40 ), 0.41 in Control vs. 0.53 in Ulcerative Colitis case; Chandigarh ( 41 ), 0.5 in Control vs. 0.64 in NAFLD case; and Lucknow, UP ( 42 ), 0.65 in healthy Control vs. 0.54 in CAD cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that by using our smartphone-based app, we were able to accurately detect serum soluble CD14 as a potential disease-activity-related biomarker of lupus [ 45 , 46 ]. sCD14 concentrations in patients with lupus nephritis were reported around 2~10 mg/L in plasma [ 47 , 48 ]. In this assay, CD14 captures the antibody and detection antibody were used to form a sandwich structure with the analyte to detect CD14 in a microarray format.…”
Section: Resultsmentioning
confidence: 99%
“…On the genetic level, a polymorphism was recognized inside the CD14 gene promoter sequence with a C–T transition at base pair-159 from the main transcription start site [ 21 ]. The wild type was (CC), while the homozygous mutant was (TT), and the heterozygous mutant was (CT) [ 22 ]. Several studies reported the association between this polymorphism and allergic diseases [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%